2000
DOI: 10.2527/2000.78112927x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake of valine by lactating porcine mammary tissue.

Abstract: The cellular uptake of branched-chain amino acids in mammary tissue is important for understanding their role in milk synthesis in the sow. This study characterized the kinetic properties and substrate specificity of the valine uptake system in the porcine mammary gland. Mammary tissue was collected from lactating sows at slaughter and tissue explants were incubated in media containing isosmotic salt and amino acids of interest, plus [3H]valine tracer. Valine uptake was time-dependent and was dependent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Positive effects of branched-chain amino acids (BCAAs) on both milk and body protein synthesis have previously been documented [17]. In porcine mammary tissue, after the addition of VAL to the culture medium, the amount of intracellular VAL exceeded the amount of extracellular VAL within 15-30 min [18]. In this experiment, only cellular protein concentrations were significantly increased after VAL treatment (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Positive effects of branched-chain amino acids (BCAAs) on both milk and body protein synthesis have previously been documented [17]. In porcine mammary tissue, after the addition of VAL to the culture medium, the amount of intracellular VAL exceeded the amount of extracellular VAL within 15-30 min [18]. In this experiment, only cellular protein concentrations were significantly increased after VAL treatment (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Uptake inhibition among AA has been shown to occur in a number of tissues, including mammary tissue, and thus may explain the curvilinear relationship between CP intake and AA a-v observed in this study, as well as that observed by Guinard and Rulquin (1994). In this study, in contrast to the cationic and small neutral AA, arterial concentrations of the large neutral AA, in particular the BCAA leucine and isoleucine, largely increased in sows fed the Excess CP diet, which may have contributed to the quadratic response, albeit a trend, between CP intake and valine a-v. For instance, uptake of valine by the lactating sow mammary tissue has been shown to be strongly inhibited by physiological concentration of leucine (Jackson et al, 2000). A similar explanation for the quadratic response in lysine a-v may be proposed, based on the findings that high concentrations of neutral AA both inhibit lysine influx into and stimulate lysine efflux from rodent mammary tissue (Shennan et al, 1994;Calvert and Shennan, 1996).…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have shown that high Leu is known to negative interaction transport of Ile and Val and enhance catabolism of Ile and Val. Leucine inhibits Val uptake in lactating porcine mammary tissue (Jackson et al, 2000) and in lactating dairy mammary tissue (Haque et al, 2013). Consequently, duodenal infusions of 40 g of Leu/d to corn-based diets improved both milk protein content and yield on diets limiting in Lys or Met (Rulquin and Pisulewski, 2006).…”
Section: Discussionmentioning
confidence: 99%